Development of dissolution tests for the quality control of complementary/alternate and traditional medicines: Application to African potato products - Nair, Vipin Devi Prasad; Kanfer, Isadore (Journal of Pharmacy & Pharmaceutical Sciences, 2008)
ABSTRACT - Purpose: Unlike orthodox medicines, specific guidelines for dissolution testing of complementary/alternate (CAMs) and traditional medicines (TMs) have not been developed nor is dissolution testing a requirement for the quality control of such products. In this report, the dissolution of African Potato (AP) products, an African traditional medicine (ATM) which has been ingested by man for a diversity of ailments, has been investigated. A norlignan glycoside namely hypoxoside and a sterol, ?-sitosterol (BSS) are purported to be the most important phytochemicals in marketed products of AP. Dissolution testing of AP products containing labelled content of sterols and those containing only hypoxoside is proposed whereby BSS and hypoxoside are monitored as markers for the release of the contents of the abovementioned products, respectively. Methods: The FDA dissolution guidance for industry was used to study the best dissolution condition for several formulations of AP. Buffers in the range of pH 1.2 to 7.5 were used to investigate the dissolution of AP products containing hypoxoside as a marker compound. Similarly, biorelevant dissolution media such as fasted state simulation fluid (FaSSIF) and fed state simulation fluid (FeSSIF) at different pH were used to investigate the release of BSS in AP formulations labelled to contain sterols which exhibited poor water solubility. Results: Dissolution testing of AP products containing hypoxoside, conducted at pH 1.2 using USP Apparatus 1 indicated that more than 75% of hypoxoside was released within 1 hr. Dissolution testing of products containing sterols, conducted in FeSSIF at a pH of 5.0 resulted in a release of at least 75% of BSS after 1 hr for all but one of the products tested. Conclusions: Dissolution testing conditions have been developed for AP products containing two different marker compounds where one of the components, hypoxoside, is water soluble, whereas another component, BSS is poorly water soluble. This necessitated the use of different dissolution media and pHs in order to monitor the respective release of hypoxoside and BSS from AP products. The results of this study indicate the necessity and possibility of developing appropriate dissolution testing procedures for use in the quality control of CAMs/TMs.